2021
DOI: 10.3389/fmats.2020.622479
|View full text |Cite
|
Sign up to set email alerts
|

Stability Evaluation and Mechanism of Asphalts Modified With Various Rubber Powder Contents

Abstract: Ground tires are one of the main sources of urban solid waste. Rubber powder-modified asphalt provides an effective method to solve the problem, and it presents good high- and low-temperature performance in sustainable pavement construction. However, the storage properties of rubber powder-modified asphalts prepared from the traditional low-temperature shear mixing method are unstable, which restricts their application. In this study, four test methods (the softening-point test; the dynamic shear rheological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Brookfield rotational viscosity and softening point are more reasonable characterization methods for determining the high-temperature performance index of CR-modified asphalt, whereas the low-temperature performance is characterized by the 5 °C ductility test [ 30 ]. Figure 7 shows the performance indexes of LRMA and pure AO modification.…”
Section: Resultsmentioning
confidence: 99%
“…Brookfield rotational viscosity and softening point are more reasonable characterization methods for determining the high-temperature performance index of CR-modified asphalt, whereas the low-temperature performance is characterized by the 5 °C ductility test [ 30 ]. Figure 7 shows the performance indexes of LRMA and pure AO modification.…”
Section: Resultsmentioning
confidence: 99%
“…Plenty of earlier experiments [18][19][20][21][22][23][24] also suggested that it was possible to effectively improve cementation between rubber powders and cement and increase the flexural and compressive strength of rubber cement-based composite materials by giving specific treatments to the surface of rubber powders. For example, Senouci et al removed the stains on the surface of rubber powders simply by soaking and rinsing; Rostami et al soaked and cleaned the rubber powders with distilled water, CCl 4 reagent, and organic mixed emulsion.…”
Section: Introductionmentioning
confidence: 99%